1992
DOI: 10.1016/0014-5793(92)80101-l
|View full text |Cite
|
Sign up to set email alerts
|

A delayed and sustained rise of cytosolic calcium is elicited by oxidized LDL in cultured bovine aortic endothelial cells

Abstract: Bovine aortic endothelial c~lls (BAEC) pulsed for 5 h with mildly oxidized low density lipoproteins (LDL), exhibit~ a broad, sustained and high peak of [Ca:*]l occurring several hours after the end of the pulse and reachilll~ very high [Ca"+]t values (around 2500--3000 nmol/I) and a concomitant drop of eytosolic pH (around 0.2-0.3 pH units) without any loss of cell viability. When BAEC were continuously pulsed with oxidized LDL, the peak of [Ca2*]~ was more sustained than in short pulse experiments and was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 45 publications
(38 reference statements)
2
25
0
Order By: Relevance
“…However, in contrast to growth factors, moxLDL is a nonspecific mediator that triggers a broad spectrum of cellular signals. [5][6][7][8][9][10][11] For instance, moxLDL-induced PDGFR␤ activation is similar to that of EGFR, 12 thus extending the concept that moxLDL activates various tyrosine kinase receptors and suggesting that besides their classic role of transducers of growth factors signaling, PDGFR␤ and EGFR may act as cellular sensors for oxidative stress and oxidized lipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in contrast to growth factors, moxLDL is a nonspecific mediator that triggers a broad spectrum of cellular signals. [5][6][7][8][9][10][11] For instance, moxLDL-induced PDGFR␤ activation is similar to that of EGFR, 12 thus extending the concept that moxLDL activates various tyrosine kinase receptors and suggesting that besides their classic role of transducers of growth factors signaling, PDGFR␤ and EGFR may act as cellular sensors for oxidative stress and oxidized lipids.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Oxidized LDL (oxLDL) is present in atherosclerotic areas 3 and elicits changes in (1) lipoprotein metabolism (foam cells), (2) gene expression (adhesion molecules, cytokines, growth factors, coagulation proteins), (3) cell migration, motility, and contractility, (4) cell proliferation; (5) cell viability/death, and (6) local immune response. 3 OxLDL triggers or alters various signaling pathways, 5 namely calcium, 6 trimeric G proteins and cAMP, 7 phospholipase D, 8 ceramide, 9 PPAR␥, 10 and epidermal growth factor receptor (EGFR activation being associated with 4-hydroxynonenal [4-HNE] derivatization). 11 We have examined whether this concept may be extended to platelet-derived growth factor receptor ␤ (PDGFR␤), a tyrosine kinase receptor of importance in atherogenesis.…”
mentioning
confidence: 99%
“…1 Oxidized LDL (oxLDL) is taken up by macrophages via the scavenger receptors, 2 promoting foam cell formation and fatty plaque development. OxLDL acquires molecular epitopes that are cytotoxic for endothelial cells, 3 stimulate chemotaxis and recruitment of monocytes, 4 and induce macrophage proliferation. 5 In addition, oxLDL is antigenic.…”
mentioning
confidence: 99%
“…Taken together with our previous findings, the results suggest that Ca 2ϩ may play a role in regulation of homologous recombination in vivo. This role of Ca 2ϩ seems especially compelling because (i) Ca 2ϩ is known as a common intracellular regulator (24), and (ii) Ca 2ϩ concentration rises in response to DNA damage (25)(26)(27)(28)(29)(30) and during meiosis (31), at the time when homologous recombination occurs. We also found that the mechanism of Ca 2ϩ -dependent stimulation of the DNA strand exchange activity of hDmc1 protein differs significantly from that of hRad51 protein, in which inhibition of the ATPase activity plays the primary role.…”
mentioning
confidence: 99%